Robotic Nipple-Sparing Mastectomy and Immediate Breast Reconstruction With Robotic Latissimus Dorsi Flap Harvest: Technique and Results. (October 2020) - Houvenaeghel, Gilles; Cohen, Monique; Ribeiro, Sandrine Rua; Barrou, Julien; Heinemann, Mellie; Frayret, Christine; Lambaudie, Eric; Bannier, Marie
Introduction . Only few cases of robotic latissimus dorsi flap reconstruction (RLDFR) have been reported in indication of reconstruction for breast cancer (BC). We report our experience of combined robotic nipple-sparing mastectomy (R-NSM) and RLDFR, and analyze technique, indications, and reproducibility. Methods . All patients with R-NSM and RLDFR from November 2016 to August 2, 2018, were analyzed, and technics have been described. Complication rate with Clavien-Dindo grading and postoperative hospitalization length (days) are reported. Results . Thirty-five R-NSM with RLDFR were performed in 22 cases for primitive BC and 13 for local recurrence. In 12 patients, another surgical procedure was performed during the same time (axillary lymph node dissection or contralateral breast surgery). R-NSM was realized through a short axillar incision, with inside-only installation for 12 patients (34.3%): 18 nonautologous and 17 autologous RLDFR associated with implant in 9 patients. In logistic regression, mastectomy weight >330 g was significantly associated with the use of implant (odds ratio [OR] = 17, P = .015), and significant factor of the time of anesthesia ≥380 minutes was 2 installations (OR = 10.4, P = .049). The median duration of hospitalization stay was 4 days. Complications rates were 51.4% (18/35; 9 grade-1, 2 grade-2, and 7 grade-3). In logistic regression, associated other surgical procedure was predictive of grade-3 complications (OR = 6.87, P = .053). Conclusion . We confirmed the reproducibility and safety of R-NSM and RLDFR with a decreased complication rate. NSM was performed in 42.8% of our patients after previous radiotherapy. We observed an increase of grade-3 complications when R-NSM and RLDFR was combined to another surgical procedure.